Large tolerance for incidence angle in Terahertz parametric detection - Hyuga Inoue; Sota Mine; Kodo Kawase; Kosuke Murate (Scientific Reports)
Abstract In the THz parametric detection method, which detects terahertz (THz) waves by upconverting them to a near-infrared beam in a LiNbO3 crystal, it has been widely assumed that the THz waves and the pump beam must satisfy the non-collinear phase-matching condition, dictated by the law of momentum conservation, and that the incidence angle of the THz waves to the crystal must be precisely controlled. However, in this study, we discovered that THz waves can be detected even at various incidence angles to the LiNbO3 crystal that do not satisfy the non-collinear phase-matching condition. While the incidence angle tolerance for the near-infrared injection beam during THz wave generation is as narrow as 0.058 degrees, a remarkably large tolerance of approximately 116 degrees was achieved for terahertz detection. This finding also indicates that the Si prism coupler, previously considered essential for satisfying the phase-matching condition, is not necessarily required. The large incidence-angle tolerance significantly simplifies the optical setup and opens up possibilities for a wider range of application measurements.